POVERTY RATE ANALYSIS IN THE PROVINCE OF PAPUA IN 2021-2022 - Fadilah, Nur; Kirana, Tamira Pontia (Noble Cendekia Indonesia, 2024)
Poverty is defined as a condition in which a person or group of people are unable to fulfill their fundamental rights to live a life of dignity. Poverty is a very important money issue for Papua province. The purpose of this study is to categorize regions of residence in Papua province based on poverty indicators. The data used is the time series March 2021-March 2022, including the percentage of poor people, poverty severity index, and poverty depth index. Methods This research uses quantitative secondary data that has been previously collected by the Central Bureau of Statistics. The data collected is data on the poverty rate in Papua province in the period 2021 to 2022. Based on the research results, it can be concluded that the areas of residence in Papua province with the largest percentage of poor people, poverty depth index (P1), and poverty severity index (P2) are in rural areas with a percentage level of 52.39%; 8.474; 2.914 in March 2022. Meanwhile, the areas of residence in Papua province with the lowest percentage of poor people, poverty depth index (P1), and poverty severity index (P2) are in urban areas with a percentage level of 5.02%; 0.526; 0.112 respectively.